Influence of Electronic Word of Mouth (E-Wom), Product Quality and Price on Purchase Intention a Mitsubishi Type Xpander Car at PT Sun Star Motors Mitsubishi Mt Haryono Semarang - Lutfiana Kaja IP; Winarto - Winarto; Taviyastuti - Taviyastuti (Politeknik Negeri Semarang, 2021)
This study aims to empirically examine the effect of electronic word of mouth (e-WOM), product quality and price on the purchase intention of a Mitsubishi Xpander car. This analysis uses independent variables, namely the influence of electronic word of mouth (e-WOM), product quality and price. The dependent variable is purchase intention. The sample of this research is consumers who buy Mitsubishi type Xpander cars at Mitsubishi MT Haryono dealers Semarang in 2020. Data collection is done by questionnaires distributed via google form to consumers as many as 50 questionnaires. The statistical method used Multiple Linear Regression Analysis and obtained the equation Y = 0.265X1 + 0.326X2 +0.478X3. The results showed that partially electronic word of mouth (e-WOM), product quality and price had a significant and positive effect on purchase intention. Purchase intention is explained by electronic word of mouth (e-WOM), product quality and price are 73.1%, while 26.9% is explained by other variables not examined in this study.